The Contributions of MAPP–OAS to Transitional Justice in Colombia - España, Isabel Cristina (Universidad Distrital Francisco José de Caldas, 2021)
This paper analyzes the main contributions of the OAS Mission to Support the Peace Process in Colombia (MAPP–OAS) to transitional justice in Colombia, as a result of the actions by this international organization in support for the justice and peace process between 2005 and 2016. A qualitative research methodology was used, including the use of methodological tools such as: interviews and documentary analysis. Among the main findings, it was found that MAPP–OAS actions in support for the justice and peace process in Colombia contributed to: a) the strengthening of the justice and peace legal system, b) the strengthening of state institutions responsible for the process and c) the strengthening of justice and peace trials. This research offers interesting insights into the contributions of a regional organization (such as the OAS) in the implementation of transitional justice processes, while providing a starting point for the analysis of transitional justice in Colombia, in the context of the implementation of the Special Jurisdiction for Peace.